Survival Impact of Surgical Resection in Locally Advanced T4b Oral Squamous Cell Carcinoma. (18th January 2021) - Gangopadhyay, Abhishek; Bhatt, Supreet; Nandy, Kunal; Rai, Shreya; Rathod, Priyank; Puj, Ketul Sureshbhai
Abstract : Objective/Hypothesis: With non‐surgical treatment, T4b oral squamous cell carcinoma (OSCC) have an unacceptably poor prognosis. A subset of patients if selected wisely for surgery, can have significantly improved survival. The present study aims to explore the feasibility of radical resection and neoadjuvant chemotherapy (NACT) in the T4b OSCC and their impact on survival, along with the factors affecting it. Study Design: This is a retrospective analysis of 302 consecutive patients with T4b OSCC presented at our institute between July 2015 and January 2016. Methods: Three different treatment protocols were decided depending on the extent of the disease—upfront resection, NACT (followed by surgery or chemo/radiation depending on the response), or upfront non‐surgical treatment (chemotherapy and/or radiotherapy). Results: Upfront surgery was done in 67 (22.19%) patients and 155 (51.32%) patients received NACT. The rest of the patients received upfront non‐surgical treatment. The overall response rate of NACT was 23.23% and the resectability rate was 36.13%. The median OS for the whole population was 12 months (30 months for the surgical group and 9 months for the non‐surgical group). There was no survival difference between supra versus infra‐notch tumors ( P value = .552) or post‐NACT versus upfront surgery ( P value = .932). Nodal involvement was the most important poor prognostic factor affecting both DFS ( P = .006) and OS ( P = .002). Conclusions: With proper patient selection after thorough clinico‐radiological assessment, a subset of T4b OSCC can be operated with curative intention; either upfront or after downstaging with NACT, which ultimately translates into improved survival. Level of Evidence: 3 Laryngoscope, 131:E2266–E2274, 2021